Reconciling Shariah Compliance and Institutional Risk: A Maqāṣid-Based Analysis of Ḥawālah and Kafālah in Indonesian Islamic Banking - Holis Holis; Nasrulloh Nasrulloh; Sugeng Widodo; Dzikrulloh Dzikrulloh; Ach. Mus'if; Tri Pujiati; Abu Yasid; Ahmad Musadad (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The implementation of ḥawālah (transfer of debt liability) and kafālah (guarantee) in Indonesia’s Islamic banking reveals an increasing tension between formal Shariah compliance and institutional risk management imperatives. Although classically categorised as tabarruʿ-based and non-profit contracts, contemporary practices reposition them as fee-generating instruments and risk transfer mechanisms, raising concerns about substantive alignment with Islamic legal and ethical principles. This study critically examines the extent to which modern applications of ḥawālah and kafālah reflect their classical fiqh foundations and maqāṣid al-sharīʿah objectives, and analyses how regulatory frameworks and institutional risk management influence their reinterpretation. Using a normative, legal and comparative approach, the research analyses classical fiqh al-muʿāmalāt doctrines, AAOIFI Shariah standards, DSN–MUI fatwas, and Indonesia’s positive law governing Islamic banking, supplemented by semi-structured expert interviews. This analysis is based on two expert interviews with members of Shariah Supervisory Boards and DSN–MUI-affiliated practitioners involved in Islamic banking governance.The results reveal a significant conceptual and functional shift, where formal Shariah compliance often masks substantive transformation into institutional risk management tools, evidenced by fee-based structures, hybrid contractual arrangements, and standardised product designs that prioritise institutional risk governance over the original altruistic rationale of tabarruʿ. Empirical signals from the interviews indicate recurring fee structures exceeding administrative cost recovery thresholds, implicit use of ḥawālah in transfer products without explicit contractual labelling, and kafālah arrangements structured similarly to risk-priced service contracts. The study highlights the need for clearer governance standards and substantive regulatory guidance to mitigate Shariah dilution while accommodating legitimate risk management needs. From a policy perspective, regulators should establish clearer criteria for permissible fee structures and hybridisation boundaries to ensure alignment with maqāṣid al-sharīʿah while maintaining financial stability. By reconceptualising ḥawālah and kafālah as hybrid institutional contracts, this research advances a maqāṣid al-sharīʿah–oriented evaluative framework that transcends procedural conformity toward ethical and institutional coherence.